Awad Al- Qawzi and the issues of the grammatical term - Al- Mutairi, Ibrahem Humaidan (Arab Journal for Sciences and Research Publishing, 2021)
This study is to define the scientific character of Awad Algawzi, which has never been studied the way it should, for example, his social life and highlighting his books and his published researches. Not just these, but also to study some grammatical term’s cases, like Terms and Conditions of term and the attention of Grammatists to the way of choosing their grammatical terms and the way they look, This study results in those Awad Algawzi thoughts in some cases are similar to the Ancient’s thoughts, The recommendation of this study is to study his efforts that facilitated grammar.